Crystal structure of (4,4′-bipyridyl-κN)bis[N-(2-hydroxyethyl)-N-isopropyldithiocarbamato-κ2 S,S′]zinc(II)–4,4′-bipyridyl (2/1) and its isostructural cadmium(II) analogue - Tan, Yee Seng *; Tiekink, Edward R. T. * (International Union of Crystallography, 2017)
The title structures, [M(C6H12NOS2)2(C10H8N2)]·0.5C10H8N2, for M = Zn, (I), and Cd, (II), feature terminally bound 4,4′-bipyridyl ligands and non-coordinating 4,4′-bipyridyl molecules, with the latter disposed about a centre of inversion. The coordination geometry about the metal atom is defined by two non-symmetrically chelating dithiocarbamate ligands and a pyridyl N atom. The NS4 donor sets are distorted but, approximate to trigonal bipyramidal in each case. In the crystal, hydroxy-O—H...O(hydroxy) and hydroxy-O—H...N(pyridyl) hydrogen bonds between the zinc-containing molecules lead to a supramolecular layer parallel to (100). The three-dimensional architecture arises as the layers are linked via methine-C—H...S, pyridyl-C—H...O(hydroxy) and π–π [inter-centroid distance between coordinated pyridyl rings = 3.6246 (18) Å] interactions. Channels along the c-axis direction are occupied by the non-coordinating 4,4′-bipyridine molecules, which are held in place by C—H...π(chelate ring) contacts.